Light-controlled C2H2 gas sensing based on Au–ZnO nanowires with plasmon-enhanced sensitivity at room temperature. Issue 27 (15th June 2015) - Zheng, Z. Q.; Wang, B.; Yao, J. D.; Yang, G. W.
Abstract : A visible light-controlled sensing response of the Au–ZnO nanowires for C2 H2 gas at room temperature by plasmon-enhanced sensitivity. Abstract : We have experimentally demonstrated a visible light-controlled sensing response of the Au–ZnO nanowires for C2 H2 gas at room temperature by plasmon-enhanced sensitivity, in which Au nanoparticles were coated on the surface of ZnO nanowires. The ZnO nanowires without Au nanoparticles showed a normal n-type response, whereas the Au coated ZnO nanowires exhibited a concentration-dependent and time-dependent p–n transition response for the sensing response to C2 H2 gas at room temperature. This unconventional sensing behavior can be explained by the formation of a surface inversion layer. Meanwhile, this sensing can be modulated and the response was significantly enhanced at room temperature under visible light illumination. This light-controlled sensing response from the Au–ZnO nanowires was attributed to the fact that the visible light excites the surface plasmon resonance of Au nanoparticles on the surface of ZnO nanowires, and it can inject hot electrons into the conduction band of ZnO. These results hinted the potential application of the as-fabricated sensor in monitoring C2 H2 gas at room temperature, and opened up new approaches for developing a new generation of visible light modulated gas sensors.